Karst as a criterion for defining areas less suitable for agriculture - Ciglič, Rok; Hrvatin, Mauro; Komac, Blaž; Perko, Drago (Acta geographica Slovenica, 2012)
The proposed European Union indicators for defining areas less suitable for agriculture in Slovenia are not entirely appropriate because taking them into account would omit some distinctly and clearly unsuitable areas–for example, Suha krajina (Dry Carniola) and Bela krajina (White Carniola)–and farmers would be unjustifiably financially harmed. In such a case, every European Union member state has the right to propose an additional indicator to reduce such discrepancies. With regard to actual natural conditions, in Slovenia especially some karst landscapes would be unjustifiably omitted, and so we have proposed a karst indicator as an additional criterion based on the distribution of karst (i.e., carbonate) rocks. Through spatial coverage of karst rocks and soils, we determined whether more reasonable and less strict application of European criteria regarding soil could be satisfactory for better results in defining areas less suitable for agriculture in Slovenia.